Nutritional Status of Under-five Children in Northeast India: Effect of Household Socioeconomic Status (Indian Journal of Public Health Research & Development, 2020)
Aim: The study is an attempt to understand the effect of household socioeconomic status on both acute andchronic undernutrition in northeastern states of India.Methods: The study used data from the National Family Health Survey (NFHS). Distribution analysis andconcentration index were used to examine the effect of household socioeconomic status on undernutrition.The study population consists of 31,908 children under five years of age.Results: The prevalence of stunting is decreasing significantly over time. While prevalence of wasting isseen to be increasing in states like Arunachal Pradesh, Assam and Sikkim. As the socioeconomic statusof the household increases, the probability of both height-for-age and weight-for-height z-score less than-2 standard deviation decreases significantly. The variation in the distribution of z-score decreases as thehousehold socioeconomic status increases. Similarly, the value of concentration index for all the eightstates irrespective of rural-urban place of residence are negative. Except for Sikkim, the concentration ofundernourished children is higher in a household with lower socioeconomic status in urban areas compareto their counterparts in rural areas.Conclusion: The study shows the disproportionate concentration of undernutrition among the householdwith poorer socioeconomic status in northeast India. And the burden is higher in urban poor. Thus, an effortto balancing the socioeconomic inequalities accompanying with improving the accessibility of services tothe poor is necessary for improving nutritional status for children under five years of age in northeast India.
Keywords: undernutrition, socioeconomic status, northeast India, distribution analysis